Line-of-sight guided time delay control for three-dimensional coupled path following of underactuated underwater vehicles with roll dynamics. (1st July 2020) - Yu, Caoyang; Liu, Chunhu; Xiang, Xianbo; Zeng, Zheng; Wei, Zhaoyu; Lian, Lian
Abstract: This paper addresses the problem of three-dimensional (3-D) coupled path following control for a six-degrees-of-freedom underactuated underwater vehicle. To compensate for nonzero roll angle, an improved 3-D line-of-sight guidance law is proposed in the kinematic layer. Especially, this novel guidance law can be applied to not only actuated but also underactuated underwater vehicles in roll, by assigning the desired roll angle. Subsequently, a simplified time delay controller is designed in the dynamics layer to robustly track the desired guidance angle, such that the entire path following errors are bounded. Finally, comparative numerical simulation results among different following paths, initial states and controllers are provided to show the outperformance of the designed 3-D coupled path following controller. Highlights: An improved spatial LOS guidance law that considers the effect of roll is proposed for an underactuated underwater vehicle. A model-free time delay controller with few gains is designed for robust dynamics tracking. Comparative case studies validate the outperformance of the entire 3-D path-following system.